Sistem Informasi Pemasaran Perumahan Pusaka Bumi Menggunakan View 360 Berbasis WEB - Zulia Nur Permatasari zulianp; Kamdan; Dwi Sartika Simatupang (Computer Science and Information Technology, 2023)
Pusaka Bumi Housing which is under the auspices of PT. Istia Jaya Land is located at Jln. Parungkuda Scouts, Parungkuda District, Kab. Sukabumi, West Java Province. PT.Istia Jaya Land is a company engaged in the sale of houses. The housing marketing team still uses conventional methods in marketing the housing, such as still using brochures, which in general, the contents of the brochures are not in accordance, starting from the 3D house drawings, which are different from the unit designs of the original housing, and seem unrealistic, so it confuses many potential buyers. feel disinterested. so researchers designed a Housing Marketing Information System Using view 360. In making this website the aim is for housing marketing in order to increase the attractiveness of prospective buyers and also the competitiveness of the housing. Housing Marketing using View 360 Based on this website can provide unique experience benefits for prospective buyers and will also be more effective. First, by using View 360 Technology, prospective buyers can take a Virtual Tour through the housing website online, without having to physically visit the location. This allows them to view and explore every corner of the room, layout, and housing facilities from the comfort of their own home. The use of view 360 in housing marketing can increase the attractiveness of prospective buyers and the competitiveness of these housing. In a competitive environment, housing with a virtual 360 view tour has an advantage over one that only uses regular photos. This can attract potential buyers, increase the visibility of housing, and speed up the selling process. The results of this information system design are expected to be able to provide convenience in terms of promotion for Bumi Pusaka Housing.